Desain Lembar Kerja Siswa Materi Sistem Persamaan Dua Variabel Berorientasi Etnomatematika - Drajat Friansyah; Maria Luthfiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to explain the steps in designing teaching materials in the form of Ethnomatematics-oriented worksheet on SPLDV material. The method used by the author in designing teaching materials is part or two of the initial stages of the ADDIE development model which consists of the analysis, design, development, implementation, and evaluation stages. The results of the study, the concept of ethnomatematics that can be integrated into the form of worksheets, namely, the unit of calculation in the sale and purchase transactions in traditional markets in the form of